2022
DOI: 10.3390/brainsci12030404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motor and Cognitive Tasks on Time Estimation

Abstract: The passing of time can be precisely measured by using clocks, whereas humans’ estimation of temporal durations is influenced by many physical, cognitive and contextual factors, which distort our internal clock. Although it has been shown that temporal estimation accuracy is impaired by non-temporal tasks performed at the same time, no studies have investigated how concurrent cognitive and motor tasks interfere with time estimation. Moreover, most experiments only tested time intervals of a few seconds. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 72 publications
7
9
1
Order By: Relevance
“…In our previous study, for the first time, we combined time estimation of long durations (up to 2 min), four different cognitive tasks of increasing difficulty, and two different motor conditions (Castellotti et al, 2022). Our results showed that, when participants were sitting on a chair (absence of motion), they tended to underestimate durations during cognitive-demanding tasks and overestimate durations while attending only to time [in line with the attentional allocation model (Grondin, 2010;Allman et al, 2014;Matthews and Meck, 2016)].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In our previous study, for the first time, we combined time estimation of long durations (up to 2 min), four different cognitive tasks of increasing difficulty, and two different motor conditions (Castellotti et al, 2022). Our results showed that, when participants were sitting on a chair (absence of motion), they tended to underestimate durations during cognitive-demanding tasks and overestimate durations while attending only to time [in line with the attentional allocation model (Grondin, 2010;Allman et al, 2014;Matthews and Meck, 2016)].…”
Section: Introductionsupporting
confidence: 56%
“…For example, Ebersbach et al (1995) investigated the effect of different tasks (cognitive, fine motor, and combined tasks) on walking, finding that only combined mental and fine motor demands interfere with the regulation of balance during walking, suggesting that the effect of a concurrent task on gross body movements depended on the difficulty of the secondary task. On the other end, walking and balance control reduce cognitive abilities, such as solving math operations (Chong et al, 2010;Castellotti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar motor-induced visual distortions of space, time, and numerosity have also been reported during saccadic eye movement [7]. Finally, time perception is even altered during walking [8] or running [9], generalizing the sensorimotor interactions to many different motor effectors as well as to different motor routines. In brief, the internal representation of the external world can be considered an active combination of perceptual and motor information.…”
Section: Perception Action and Cognition: A Complex Interactionmentioning
confidence: 52%
“…Could the effects be attributed to the engagement of the motor system with or without negligible vestibular contribution? In a recent study, Castellotti et al ( 2022 ) found that a secondary cognitive task led to an underestimation of a given time interval between 15 and 120 s. This could be an attention effect. Walking on a treadmill, as opposed to sitting while solving arithmetic tasks, led to even more pronounced underestimation.…”
Section: Discussionmentioning
confidence: 96%